Meningkatkan Prestasi Belajar Siswa dalam Keterampilan Berpidato Bahasa Indonesia melalui Metode Pembelajaran Demonstrasi di Kelas IX.E SMP Negeri 3 Pasarkemis Semester Ganjil Tahun Pelajaran 2022/2023 - Arina Israni (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2022)
Based on the researcher's experience while teaching in Class IX.E SMP Negeri 3 Pasarkemis that some Class IX.E students did not follow the lesson well during Indonesian language lessons. The learning process is less effective due to the lack of student activity to read Indonesian language lesson material, the lack of student activity in expressing opinions during the lesson. Lack of student activity answering questions from the teacher. Lack of interest in students to take part in Indonesian language lessons. So that many students divert attention, such as chatting with their classmates, drawing, not enthusiastic when listening to the teacher explaining the lesson. This is caused by the teacher's model or way of explaining lessons that are too monotonous so that students pay less attention to the teacher during the lesson, and the learning process will not go well.